Problematikadalampenerapan Hukum Waris Islam Di Desa Sirnamanah Kecamatan Darangdan Kabupaten Purwakarta - Najib, Moch Najib Wasi'a Mubarok; Erfiansyah, Erfiansyah; Dulnasir, Dulnasir (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study aims to determine the implementation and constraints thataffect the application of Islamic inheritance law.This research is afield research, using descriptive, sociology, normative theology, historicalapproach, and presented qualitatively. The result shows that the implementation of Islamic inheritance law is carried out in kinshipprinciple. Special sections are provided for the heirs who take care of their parents and thepurabage inheritance as absolute power. The application of the law to the distribution of assets is done by dividing the heirs in kinship principle without seeing the provisions of God's law. Problems in the application of Islamic inheritance law include the customary law and poor understanding of Islamic inheritance law.